The Effect of Storage Condition on Viability of Peanut (Arachis hypogaea L.) Seeds in Relation to Its Genetic Conservation - Soebekti Soebekti (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 1987)
-